Peranan Audit Forensik Dalam Pencegahan Fraud Pada Laporan Dana Kampanye Peserta Pemilu Pasca Reformasi Di Indonesia - Aryanto Nur; Suhada . (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
Post-reform elections in Indonesia are vulnerable to fraudulent campaign finance reporting. Empirical data from the 2004–2019 elections show that the majority of campaign finance reports are non-transparent and unaccountable. Campaign funds, their management, and reporting need to be regulated to ensure that election participants are honest, orderly, fair, and free from fraud. This study aims to analyze the role of forensic audits in preventing fraud in campaign finance reports and to evaluate the effectiveness of existing oversight. The research uses a descriptive qualitative method with a phenomenological approach and a literature study design. Secondary data were analyzed descriptively and interpretively using the 5W+2H framework. Data sources include reports from public accounting firms, findings from the Election Supervisory Agency (Bawaslu), decisions on campaign finance violations for the 2004–2019 elections, and findings from the Financial Transaction Reports and Analysis Center (PPATK) for the 2024 election. The results show that the majority of election participants did not comply with campaign finance regulations, and the General Elections Commission (KPU) has not maximized its authority. PPATK revealed suspicious fund flows amounting to IDR 80.12 trillion in the 2024 elections, involving political parties, legislative candidates, and active officials. Agreed-upon procedures (AUP) audits proved inadequate to uncover modern fraud schemes. Forensic audits have proactive and reactive capabilities that general audits lack. The study concludes that forensic audits should be integrated into campaign finance regulations and offers a fraud prevention model based on a forensic audit trail. PPATK findings in March 2026 showed a 100% increase in suspicious transactions, confirming the urgency of oversight system reform. Regulatory revisions are needed to mandate forensic audits and grant investigative authority to Bawaslu.